STRATEGI PENINGKATAN MINAT BELAJAR DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Sumiati; Asih Marwati; Lilis Kholisoh Nuryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses innovative teaching strategies that have proven effective in enhancing students' interest and academic achievement. One of the effective approaches is Project-Based Learning (PjBL), which increases students' active participation, encourages collaboration, and deepens their understanding of the material. In addition, the performance of teachers as facilitators, motivators, and guides plays a crucial role in creating a supportive learning environment. Key components of teacher performance include using innovative methods, providing constructive feedback, and effective classroom management. The use of technology in teaching has also been shown to enhance students' learning interest by creating a more interactive and engaging learning experience. A comprehensive approach involving professional teachers, appropriate teaching strategies, and the utilization of technology can significantly improve students' interest and academic achievement.